PENGARUH PROFITABILITAS, LEVERAGE, DAN BIAYA OPERASIONAL TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Allivia Ayuningtyas; Anita Wijayanti; Yuli Chomsatu (PROSIDING, 2021)
Many companies do not have a CSR program for the community, because the company considers it a burden. But actually, CSR companies that are given to the community make a good contribution, namely reducing operational costs and a good image because it can increase the prosperity of the local community. The purpose of this study was to analyze the effect of Corporate Social Responsibility on ROA Profitability, ROE Profitability, Leverage, and Operational Costs (OER) in manufacturing companies listed on the IDX in 2017-2019. The sample was taken using purposive sampling. totaling 44 companies. The data analysis technique in this research is multiple linear analysis. The results of the study are ROA, ROE, Leverage affects Corporate Social Responsibility, while OER or operational costs do not affect Corporate Social Responsibility. Keywords: CSR, Leverage, ROA, ROE, Operational Costs.